Enhancing English Language Skills For Multimodal Transportation Professionals: A Curriculum Development Approach - Marudut Bernadtua Simanjuntak (International Journal of Educational Technology and Society, 2024)
This research explores the development and evaluation of a specialised English language curriculum for students in the field of multimodal transportation. Through qualitative analysis involving 100 cadets, the study identifies the specific language skills essential for success in this dynamic industry, including speaking, listening, reading, and writing. Based on these findings, a curriculum is designed to enhance students' proficiency and confidence in using English for various transportation-related tasks. The curriculum incorporates industry-relevant content and interactive instructional methods, such as role-plays and simulations, to provide students with practical skills applicable to real-world transportation scenarios. Pre- and post-curriculum assessments, along with feedback from students and instructors, demonstrate a significant improvement in students' language proficiency and confidence after completing the curriculum. The study also analyses the implications of English Language Teaching (ELT) and English for Specific Purposes (ESP) linguistics in designing a curriculum tailored to the needs of multimodal transportation professionals. The research contributes to the advancement of English language education within the transportation sector, offering insights for curriculum development and improvement.